High-strength silane modified polyether sealant as well as preparation method and application thereof

By using fillers such as carbon black, nano calcium carbonate and gas-phase white carbon black in silane-modified polyether sealant and reasonably preparing components, the problem of low mechanical properties of the sealant is solved, and high strength and excellent viscosity are achieved Connection performance and good durability.

CN119432291APending Publication Date: 2025-02-14HANGZHOU ZHIJIANG SILICONE CHEM +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411728829.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing silane-modified polyether sealants have low mechanical properties and insufficient shear strength and hardness, resulting in poor bonding performance and insufficient durability in the bonding and sealing applications of automotive windshields.

Method used

Carbon black is used as the reinforcement filler, nano calcium carbonate and gas-phase white carbon black are used as auxiliary reinforcement filler, and are distributed through reasonable proportions, including silane coupling agent, silane modified polyether resin, ultraviolet absorber, light Stabilizer, antioxidant, water removal agent and catalyst to prepare high-strength silane-modified polyether sealant.

Benefits of technology

The viscosity, tensile strength, hardness and shear strength of the sealant are improved, the adhesive performance to metal substrates is enhanced, the bubble problem of traditional sealant under high temperature and high humidity conditions is solved, and environmentally friendly performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159804950000171
    Figure BDA0005159804950000171
  • Figure BDA0005159804950000181
    Figure BDA0005159804950000181
Patent Text Reader

Abstract

The invention provides a high-strength silane modified polyether sealant as well as a preparation method and application thereof. The high-strength silane modified polyether type sealant is prepared from the following components in parts by weight: 290 to 360 parts of silane modified polyether resin, 150 to 200 parts of environment-friendly plasticizer, 300 to 400 parts of nano calcium carbonate, 100 to 110 parts of carbon black, 10 to 30 parts of fumed silica, 3 to 5 parts of ultraviolet light absorber, 3 to 5 parts of light stabilizer, 3 to 5 parts of antioxidant, 15 to 20 parts of dewatering agent, 15 to 25 parts of silane coupling agent and 4 to 6 parts of catalyst. The high-strength silane modified polyether sealant provided by the invention has the characteristics of high viscosity, high tensile strength, high hardness, high shear strength and good adhesion to metal substrates, and is suitable for being applied to construction process places requiring high viscosity and instant positioning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyether sealants, and specifically relates to a high-strength silane-modified polyether sealant and a preparation method and application thereof. Background Art

[0002] Car windshield adhesive is very important for the safe driving of the car. When hit, the car windshield will absorb huge impact force, and at the same time must be firmly bonded to the car body and cannot fly off the car body; when a traffic accident occurs, the firmly bonded windshield must have sufficient strength to support and protect the safety of passengers. Therefore, the sealant is required to have high strength, high hardness, tear resistance, excellent sealing performance, and can improve the overall rigidity of the car body.

[0003] CN104099059A discloses a silicone sealant for automobile side windshields and a preparation method thereof. The silicone sealant for automobile side windshields comprises the following components in parts by weight: 100 parts by weight of α,ω-dihydroxy polysiloxane, 10-60 parts by weight of modified silica, 0.5-2 parts by weight of a crosslinking agent, 0.1-0.5 parts by weight of a catalyst, and 5-20 parts by weight of methyl silicone oil. The silicone sealant for automobile side windshields provided by the technical solution is easy to use, has good adhesion to various substrates, has good weather resistance, and cures quickly, but its tensile bonding strength is still relatively low and needs to be further improved.

[0004] CN116376503A discloses a polyurethane sealing adhesive for automobile glass and its preparation method and application. The polyurethane sealing adhesive for automobile glass comprises the following raw materials in parts by weight: 50-60 parts of polyurethane prepolymer, 35-50 parts of filler, 0.3-0.5 parts of catalyst I, 0.5-2 parts of PTSI, 0.3-0.5 parts of silane coupling agent, and 15-20 parts of plasticizer; the polyurethane prepolymer comprises 10-20 parts of isocyanate, 80-110 parts of polyol, 5-10 parts of plasticizer, 0.01-0.02 parts of catalyst II, 0.2-0.4 parts of silane coupling agent, and 0.01-0.02 parts of PTSI. The one-component polyurethane sealing adhesive provided by the technical solution has high initial bonding strength and is used to bond smooth and non-porous substrate surfaces to achieve rapid positioning of glass on automobile bodies, but the bonding strength still needs to be further improved, and the heat resistance of polyurethane sealants is poor, and bubbles are prone to appear under high temperature and high humidity conditions.

[0005] Therefore, it is necessary to develop a high-strength silane-modified polyether sealant with high shear strength, high hardness, good bonding performance, and the ability to achieve rapid positioning of glass. Summary of the invention

[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a high-strength silane-modified polyether sealant and a preparation method thereof, wherein the high-strength silane-modified polyether sealant has the characteristics of high viscosity, high tensile strength, high hardness, high shear strength and good adhesion to metal substrates.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a high-strength silane-modified polyether sealant, wherein the high-strength silane-modified polyether sealant comprises the following components by weight: 290 to 360 parts (e.g., 300 parts, 310 parts, 320 parts, 330 parts, 340 parts, or 350 parts) of a silane-modified polyether resin, 150 to 200 parts (e.g., 155 parts, 160 parts, 165 parts, 170 parts, 175 parts, 180 parts, 185 parts, 190 parts, or 195 parts) of an environmentally friendly plasticizer; ), 300-400 parts of nano calcium carbonate (for example, 310 parts, 320 parts, 330 parts, 340 parts, 350 parts, 360 parts, 370 parts, 380 parts or 390 parts, etc.), 100-110 parts of carbon black (for example, 101 parts, 102 parts, 103 parts, 104 parts, 105 parts, 106 parts, 107 parts, 108 parts or 109 parts, etc.), 10-30 parts of fumed silica (for example, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, etc.), 6 or 28 parts, etc.), ultraviolet absorber 3 to 5 parts (for example, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.2 parts, 4.4 parts, 4.6 parts or 4.8 parts, etc.), light stabilizer 3 to 5 parts (for example, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.2 parts, 4.4 parts, 4.6 parts or 4.8 parts, etc.), antioxidant 3 to 5 parts (for example, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.2 parts, 4.4 parts, 4.6 parts or 4.8 parts, etc.), 15-20 parts of dewatering agent (for example, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts or 19.5 parts, etc.), 15-25 parts of silane coupling agent (for example, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts or 24 parts, etc.) and 4-6 parts of catalyst (for example, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5.0 parts, 5.2 parts, 5.4 parts, 5.6 parts or 5.8 parts, etc.).

[0009] In the present invention, carbon black is used as reinforcing filler, nano calcium carbonate and fumed silica are used as auxiliary reinforcing fillers, and a reasonable proportion of silane coupling agent, silane-modified polyether resin, ultraviolet absorber, light stabilizer, antioxidant, dewatering agent and catalyst are compounded. Through the coordination of each component, the high-strength silane-modified polyether sealant prepared has high viscosity, short surface drying time and fast curing speed, and is suitable for use in construction process sites requiring high viscosity and instant positioning, such as windshield bonding and sealing of vehicles, high-speed railways, aerospace, and military series. The high-strength silane-modified polyether sealant has high tensile strength, high hardness, high shear strength, and good adhesion to metal substrates, which solves the problems of low mechanical properties, low shear strength, low hardness, and poor adhesion of traditional silane-modified polyether sealants; it can have excellent bonding effects on stainless steel substrates and aluminum substrates under primer-free construction conditions; the high-strength silane-modified polyether sealant has excellent weather resistance, aging performance, excellent tensile and compression recovery, etc. The high-strength silane-modified polyether sealant does not contain solvents, isocyanates, or PVC, is non-toxic, odorless, pollution-free, and environmentally friendly, solidifies when exposed to moisture in the air, has relatively simple raw material components, and has a relatively moderate raw material cost, and can be mass-produced.

[0010] Preferably, the silane-modified polyether resin is a dimethoxysilane-terminated polyether resin.

[0011] Preferably, the viscosity of the silane-modified polyether resin at 25° C. is 10,000 to 80,000 MPa·s, for example, 20,000 MPa·s, 30,000 MPa·s, 40,000 MPa·s, 50,000 MPa·s, 60,000 MPa·s or 70,000 MPa·s.

[0012] Preferably, the modified silane polyether resin includes any one of SAX400 of Zhongyuan Chemical, SAX750 of Zhongyuan Chemical, S303H of Zhongyuan Chemical, S203H of Zhongyuan Chemical, HMS-1063 of Zhejiang Huangma Technology, HMS-1107 of Zhejiang Huangma Technology, HMS-1167 of Zhejiang Huangma Technology or HMS-1267 of Zhejiang Huangma Technology, or a combination of at least two thereof.

[0013] Preferably, the environmentally friendly plasticizer includes any one of polyether polyol, di(2-propylheptyl)phthalate (DIDP) or diisononyl phthalate (DINP) or a combination of at least two thereof.

[0014] Preferably, the polyether polyol is polyether polyol C2020.

[0015] Preferably, the nano calcium carbonate is active nano calcium carbonate.

[0016] Preferably, the whiteness of the active nano-calcium carbonate is 95% to 99%, for example, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99% or 99.5%, etc.

[0017] Preferably, the specific surface area of ​​the active nano calcium carbonate is 15 to 20 m 2 / g, for example 15.5m 2 / g, 16m 2 / g, 16.5m 2 / g, 17m 2 / g, 17.5m 2 / g, 18m 2 / g, 18.5m 2 / g, 19m 2 / g or 19.5m 2 / g, etc.

[0018] Preferably, the oil absorption value of the active nano-calcium carbonate is 20-30 mL / 100 g, for example, 21 mL / 100 g, 22 mL / 100 g, 23 mL / 100 g, 24 mL / 100 g, 25 mL / 100 g, 26 mL / 100 g, 27 mL / 100 g, 28 mL / 100 g or 29 mL / 100 g, etc.

[0019] Preferably, the active nano-calcium carbonate includes any one of Japan Shiraishi CCR, Japan Zhuyuan SP, Guangxi Warner P150, Omya OMY 2T, Omya OMY 120 or Omya OMY 160, or a combination of at least two thereof.

[0020] Preferably, the carbon black includes any one of HZ6004 series carbon black, HZ630 series carbon black, HZ7100 series carbon black or Orylon H30 carbon black, or a combination of at least two thereof.

[0021] In the present invention, the carbon black has a high specific surface area, is powdery, has good stability, has high tinting power and low viscosity, and has good fluidity and dispersibility.

[0022] Preferably, the specific surface area of ​​the fumed silica is 140 to 200 m 2 / g, for example 145m 2 / g, 150m 2 / g, 155m 2 / g, 160m 2 / g, 165m 2 / g, 170m 2 / g, 175m 2 / g, 180m 2 / g, 185m 2 / g, 190m 2 / g or 195m 2 / g, etc.

[0023] In the present invention, the specific surface area of ​​the fumed silica increases, which can improve the tensile strength and elongation at break of the one-component silane-modified polyether sealant and has a good reinforcement effect. At the same time, the increase in specific surface area increases the viscosity of the one-component silane-modified polyether sealant.

[0024] In the present invention, the fumed silica is powdered fumed silica with a high specific surface area.

[0025] Preferably, the fumed silica includes any one of Tokuyama QS-10, Tokuyama QS-102, Tokuyama QS-10LS, Cabot LM-150 or Evonik R-974, or a combination of at least two thereof.

[0026] Preferably, the ultraviolet absorber includes any one of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (UV-326), 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole or 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, or a combination of at least two thereof.

[0027] Preferably, the light stabilizer includes any one of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (UV-292), bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidine) succinate or poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]} or a combination of at least two thereof.

[0028] Preferably, the antioxidant includes any one or a combination of at least two of glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate (antioxidant 245), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] or tris[2,4-di-tert-butylphenyl] phosphite.

[0029] Preferably, the desiccant comprises vinyltrimethoxysilane (A-171) and / or vinyltriethoxysilane.

[0030] Preferably, the silane coupling agent includes any one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (A-1120), N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, oligomeric bisaminosilane, multifunctional aminosilane oligomer, triaminotrimethoxysilane or bis(trimethoxysilylpropyl)amine, or a combination of at least two thereof.

[0031] Preferably, the catalyst comprises any one or a combination of at least two of dibutyltin bis(acetylacetonate) (U-220H), dibutyltin dilaurate, dibutylbis(2,4-glutarato-O,O')-(OC-6-11)-tin or a reaction product of tetraethyl silicate and bis(acetyloxy)dibutyltinane.

[0032] In a second aspect, the present invention provides a method for preparing the high-strength silane-modified polyether sealant as described in the first aspect, wherein the high-strength silane-modified polyether sealant comprises the following steps: the high-strength silane-modified polyether sealant comprises the following steps: mixing a silane-modified polyether resin, an environmentally friendly plasticizer, nano-calcium carbonate, carbon black, fumed silica, an ultraviolet absorber, a light stabilizer, an antioxidant, a water scavenger, a silane coupling agent and a catalyst to obtain the high-strength silane-modified polyether sealant.

[0033] Preferably, the high-strength silane-modified polyether sealant specifically comprises the following steps:

[0034] (1) Mixing silane-modified polyether resin, nano-calcium carbonate, carbon black, and fumed silica to obtain a first mixture.

[0035] (2) The first mixture obtained in step (1), an environmentally friendly plasticizer, an ultraviolet absorber, a light stabilizer and an antioxidant are mixed to obtain a second mixture.

[0036] (3) Mixing the second mixture obtained in step (2) with a dehydrating agent to obtain a third mixture.

[0037] (4) Mixing the third mixture obtained in step (3) with a silane coupling agent to obtain a fourth mixture.

[0038] (5) Mixing the fourth mixture obtained in step (4) with a catalyst to obtain the high-strength silane-modified polyether sealant.

[0039] Preferably, the mixing in step (1) is carried out under a vacuum degree of -0.09 to 0.1 MPa (e.g., -0.08 MPa, -0.05 MPa, -0.02 MPa, 0.01 MPa, 0.04 MPa or 0.07 MPa, etc.).

[0040] Preferably, the mixing temperature in step (1) is 0-50°C, for example, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C or 45°C.

[0041] Preferably, the mixing in step (1) is stirring mixing, and the stirring speed is 900-1000 r / min (for example, 910 r / min, 920 r / min, 930 r / min, 940 r / min, 950 r / min, 960 r / min, 970 r / min, 980 r / min or 990 r / min, etc.), and the time is 30-40 min (for example, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min or 39 min, etc.).

[0042] Preferably, the mixing in step (2) comprises stirring and mixing at 0 to 50° C. (e.g., 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., or 45° C., etc.) and a rotation speed of 900 to 1000 r / min (e.g., 910 r / min, 920 r / min, 930 r / min, 940 r / min, 950 r / min, 960 r / min, 970 r / min, 980 r / min, or 990 r / min, etc.) for 5 to 12 min (e.g., 6 min, 7 min, 8 min, 9 min, 10 min, or 11 min, etc.), and then heating to 110 to 130° C. (e.g., 112° C., 114° C., 116° C., 118° C., 120° C., 122 ℃, 124℃, 126℃ or 128℃, etc.), under the conditions of a vacuum degree of -0.09 to 0.1MPa (for example, -0.08MPa, -0.05MPa, -0.02MPa, 0.01MPa, 0.04MPa or 0.07MPa, etc.) and a rotation speed of 150 to 250r / min (for example, 160r / min, 170r / min, 180r / min, 190r / min, 200r / min, 210r / min, 220r / min, 230r / min or 240r / min, etc.), stirring and mixing for 2 to 3h (for example, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h or 2.9h, etc.).

[0043] Preferably, the mixing in step (3), step (4) and step (5) is each independently carried out under a vacuum degree of -0.09 to 0.1 MPa (e.g., -0.08 MPa, -0.05 MPa, -0.02 MPa, 0.01 MPa, 0.04 MPa or 0.07 MPa, etc.).

[0044] Preferably, the mixing temperatures in step (3), step (4) and step (5) are each independently ≤45°C (eg, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C, etc.).

[0045] Preferably, the mixing in step (3) is stirring mixing, the stirring mixing speed is 400-500 r / min (for example, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min or 490 r / min, etc.), and the stirring mixing time is 10-18 min, for example, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min or 17 min, etc.

[0046] Preferably, the mixing in step (4) is stirring mixing, the stirring mixing speed is 400-500 r / min (for example, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min or 490 r / min, etc.), and the stirring mixing time is 10-18 min, for example, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min or 17 min, etc.

[0047] Preferably, the mixing in step (5) is stirring mixing, the stirring mixing speed is 400-500 r / min (for example, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min or 490 r / min, etc.), and the stirring mixing time is 5-12 min, for example, 6 min, 7 min, 8 min, 9 min, 10 min or 11 min, etc.

[0048] In a third aspect, the present invention provides a use of the high-strength silane-modified polyether sealant as described in the first aspect in windshield bonding.

[0049] In the present invention, the high-strength silane-modified polyether sealant has high viscosity and can be neutrally cured, and is suitable for use in construction process sites that require high viscosity requirements, high tensile strength and shear strength requirements, and instant positioning, such as windshield bonding and sealing of vehicles, high-speed railways, aerospace, and military series. The high-strength silane-modified polyether sealant improves the complex construction process of traditional polyurethane sealants for windshields, can achieve a primer-free bonding effect, improves the bubble problem of traditional polyurethane sealants for windshields under high temperature and high humidity conditions, and also improves the environmental protection problem of traditional polyurethane sealants for windshields.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The present invention uses carbon black as reinforcing filler, nano calcium carbonate and fumed silica as auxiliary reinforcing filler, and compound reasonable proportions of silane coupling agent, silane modified polyether resin, ultraviolet absorber, light stabilizer, antioxidant, dewatering agent and catalyst. Through the coordination of each component, the prepared high-strength silane modified polyether sealant has the characteristics of high viscosity, short surface drying time, fast curing speed, high tensile strength, high hardness, high shear strength and good adhesion to metal substrates. The viscosity of the high-strength silane modified polyether sealant is 260000-345000mpa·s, the tensile strength is 3.1-4.6MPa, the elongation at break is 180%-300%, the shear strength of 304 stainless steel is 3.8-6.5MPa, and the hardness is 62-68HA. It is suitable for use in construction process sites that require high viscosity and instant positioning, such as windshield bonding and sealing of vehicles, high-speed railways, aerospace, and military series. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] Some of the raw materials for the following examples and comparative examples are as follows:

[0054] Active nano calcium carbonate: Japan Bamboo SP, whiteness> 90%, measured 98%, specific surface area 16.0±3m 2 / g, measured 15m 2 / g, oil absorption value is 24.0±2mL / 100g, and the actual measurement is 23mL / 100g;

[0055] Active nano calcium carbonate: Guangxi Huana P150, whiteness ≥95%, specific surface area 17.5-19.5m 2 / g, oil absorption value is 27.0±3mL / 100g;

[0056] Active nano calcium carbonate: OMY 160, whiteness> 90%, specific surface area 15.0±5m 2 / g, oil absorption value is 25.0±2mL / 100g;

[0057] Carbon black: HZ6004 series carbon black, manufacturer: Tangyin Hangzhou New Materials Co., Ltd.;

[0058] Carbon black: HZ630 series carbon black, manufacturer: Tangyin Hangzhou New Materials Co., Ltd.;

[0059] Fumed silica: Evonik R-974, with a specific surface area of ​​150-190m 2 / g, measured 175m 2 / g;

[0060] Fumed silica: Cabot LM-150, with a specific surface area of ​​150±15m 2 / g;

[0061] Fumed silica: Japan Tokuyama QS-10, with a specific surface area of ​​140±20m 2 / g.

[0062] Example 1

[0063] The present embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The high-strength silane-modified polyether sealant comprises the following components by weight: 360 parts of silane-modified polyether resin (SAX400 from Zhongyuan Chemical), 150 parts of an environmentally friendly plasticizer (polyether polyol C2020), and active nano-calcium carbonate (Japan Takenori SP, with a whiteness of >90%, measured at 98%, and a specific surface area of ​​16.0±3 m 2 / g, measured 15m 2 / g, oil absorption value is 24.0±2mL / 100g, measured 23mL / 100g) 325 parts, carbon black (HZ6004 series carbon black) 110 parts, fumed silica (Evonik R-974) 30 parts, ultraviolet absorber (UV-326) 3 parts, light stabilizer (UV-292) 3 parts, antioxidant (antioxidant 245) 4 parts, dewatering agent (A-171) 15 parts, silane coupling agent (A-1120) 20 parts and catalyst (U-220H) 5 parts.

[0064] The preparation method of the high-strength silane-modified polyether sealant is as follows:

[0065] (1) Adding silane-modified polyether resin, active nano-calcium carbonate, carbon black and fumed silica in a planetary stirring kettle in sequence, evacuating the mixture, stirring and mixing at high speed for 35 min at 25° C. and a vacuum degree of −0.09 MPa, with a stirring speed of 900 r / min, taking a sample and scraping to check the appearance of the paste, the surface of which was fine and free of particles, to obtain a first mixture;

[0066] (2) adding an environmentally friendly plasticizer, an ultraviolet absorber, a light stabilizer and an antioxidant to the first mixture obtained in step (1) in sequence, stirring and mixing at high speed for 10 min at 25° C., the stirring speed is 900 r / min, the temperature is raised to 120° C., and stirring and mixing at low speed for 2.5 hours at a stirring speed of 200 r / min under a vacuum degree of -0.09 MPa, to obtain a second mixture;

[0067] (3) cooling the second mixture obtained in step (2) to 40° C., filling with nitrogen to reduce the pressure, adding a dehydrating agent, evacuating, and stirring at medium speed for 15 min at 40° C. and a vacuum degree of -0.09 MPa at a speed of 500 r / min to obtain a third mixture;

[0068] (4) filling with nitrogen to reduce the pressure, adding a silane coupling agent to the third mixture obtained in step (3), evacuating the mixture, stirring and mixing at a medium speed of 500 r / min at 40° C. and a vacuum degree of −0.09 MPa for 15 min, to obtain a fourth mixture;

[0069] (5) Inflate with nitrogen to reduce the pressure, add a catalyst to the fourth mixture obtained in step (4), evacuate, and stir and mix at medium speed for 10 min at 40° C. and a vacuum degree of -0.09 MPa. The stirring speed is 400 r / min, and the formed paste is uniform, fine, and free of particles and gel, thereby obtaining the high-strength silane-modified polyether sealant.

[0070] Example 2

[0071] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Example 1 is that the weight fraction of the silane-modified polyether resin (SAX400 produced by Zhongyuan Chemical) is adjusted to 300 parts and the weight fraction of the carbon black (HZ6004 series carbon black) is adjusted to 100 parts. Other conditions are the same as those in Example 1.

[0072] Example 3

[0073] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Example 1 is that the weight fraction of the silane-modified polyether resin (SAX400 of Zhongyuan Chemical) is adjusted to 300 parts, the weight fraction of the environmentally friendly plasticizer (polyether polyol C2020) is adjusted to 160 parts, and the weight fraction of carbon black (HZ6004 series carbon black) is adjusted to 100 parts. Other conditions are the same as those in Example 1.

[0074] Example 4

[0075] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Example 1 is that the weight fraction of the silane-modified polyether resin (SAX400 of Zhongyuan Chemical) is adjusted to 300 parts, the weight fraction of the environmentally friendly plasticizer (polyether polyol C2020) is adjusted to 180 parts, and the weight fraction of carbon black (HZ6004 series carbon black) is adjusted to 100 parts. Other conditions are the same as those in Example 1.

[0076] Example 5

[0077] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight portion of active nano calcium carbonate (Japanese Bamboo Source SP) is adjusted to 300 parts, and other conditions are the same as those in embodiment 1.

[0078] Example 6

[0079] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight portion of active nano calcium carbonate (Japanese Bamboo Source SP) is adjusted to 350 parts, and other conditions are the same as those in embodiment 1.

[0080] Example 7

[0081] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight portion of active nano calcium carbonate (Japanese Bamboo Source SP) is adjusted to 400 parts, and other conditions are the same as those in embodiment 1.

[0082] Example 8

[0083] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the weight fraction of carbon black (HZ6004 series carbon black) is adjusted to 105 parts, and other conditions are the same as those in Embodiment 1.

[0084] Example 9

[0085] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the weight fraction of carbon black (HZ6004 series carbon black) is adjusted to 100 parts, and other conditions are the same as those of Embodiment 1.

[0086] Example 10

[0087] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the weight fraction of fumed silica (Evonik R-974) is adjusted to 20 parts, and other conditions are the same as those in Embodiment 1.

[0088] Embodiment 11

[0089] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the weight fraction of fumed silica (Evonik R-974) is adjusted to 10 parts, and other conditions are the same as those in Embodiment 1.

[0090] Example 12

[0091] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight fraction of the silane coupling agent (A-1120) is adjusted to 15 parts, and other conditions are the same as those in embodiment 1.

[0092] Embodiment 13

[0093] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the weight fraction of the silane coupling agent (A-1120) is adjusted to 25 parts, and other conditions are the same as those in embodiment 1.

[0094] Embodiment 14

[0095] The present embodiment provides a one-component silane-modified polyether sealant and a preparation method thereof. The one-component silane-modified polyether sealant includes the following components in parts by weight: 360 parts of silane-modified polyether resin (SAX750 from Zhongyuan Chemical), 150 parts of environmentally friendly plasticizer (di(2-propylheptyl)phthalate), 325 parts of active nano-calcium carbonate (Guangxi Warner P150), 110 parts of carbon black (Olilong H30 carbon black), 30 parts of fumed silica (Cabot LM-150), 5 parts of ultraviolet absorber (UV-326), 4 parts of light stabilizer (UV-292), 3 parts of antioxidant (antioxidant 245), 18 parts of dewatering agent (A-171), 20 parts of silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) and 4 parts of catalyst (dibutyltin dilaurate).

[0096] The preparation method of the high-strength silane-modified polyether sealant is as follows:

[0097] (1) Adding silane-modified polyether resin, active nano-calcium carbonate, carbon black and fumed silica in a planetary stirring kettle in sequence, evacuating the mixture, stirring and mixing at high speed for 30 min at 30° C. and a vacuum degree of 0.05 MPa, with a stirring speed of 1000 r / min, taking a sample and scraping to check the appearance of the paste, the surface of which was fine and free of particles, to obtain a first mixture;

[0098] (2) adding an environmentally friendly plasticizer, an ultraviolet absorber, a light stabilizer and an antioxidant to the first mixture obtained in step (1) in sequence, stirring and mixing at high speed for 10 min at 30° C., the stirring speed is 1000 r / min, heating to 120° C., stirring and mixing at low speed for 3 hours at a stirring speed of 150 r / min under a vacuum degree of 0.05 MPa, to obtain a second mixture;

[0099] (3) cooling the second mixture obtained in step (2) to 30° C., filling with nitrogen to reduce the pressure, adding a dehydrating agent, evacuating, and stirring at medium speed for 15 min at 30° C. and a vacuum degree of 0.05 MPa at a speed of 400 r / min to obtain a third mixture;

[0100] (4) filling with nitrogen to reduce the pressure, adding a silane coupling agent to the third mixture obtained in step (3), evacuating the mixture, stirring and mixing at a medium speed of 400 r / min at 30° C. and a vacuum degree of 0.05 MPa for 15 min, and obtaining a fourth mixture;

[0101] (5) Inflate with nitrogen to reduce the pressure, add a catalyst to the fourth mixture obtained in step (4), evacuate, and stir and mix at medium speed for 10 min at 30° C. and a vacuum degree of 0.05 MPa. The stirring speed is 400 r / min, and the formed paste is uniform, fine, and free of particles and gel, thereby obtaining the high-strength silane-modified polyether sealant.

[0102] Embodiment 15

[0103] The present embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The high-strength silane-modified polyether sealant comprises the following components by weight: 360 parts of silane-modified polyether resin (Zhejiang Royal Madrid Technology HMS-1167), 150 parts of environmentally friendly plasticizer (diisononyl phthalate), 325 parts of active nano calcium carbonate (Omiya OMY160), 110 parts of carbon black (HZ630 series carbon black), 30 parts of fumed silica (Evonik R-974), and ultraviolet light. 4 parts of absorbent (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole), 5 parts of light stabilizer (bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate), 5 parts of antioxidant (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), 20 parts of dewatering agent (vinyltriethoxysilane), 20 parts of silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) and 4 parts of catalyst (U-220H).

[0104] The preparation method of the high-strength silane-modified polyether sealant is as follows:

[0105] (1) Adding silane-modified polyether resin, active nano-calcium carbonate, carbon black and fumed silica in a planetary stirring kettle in sequence, evacuating the mixture, stirring and mixing at high speed for 40 min at 25° C. and a vacuum degree of 0.01 MPa, with a stirring speed of 950 r / min, taking a sample and scraping to check the appearance of the paste, the surface of the paste was fine and free of particles, thereby obtaining a first mixture;

[0106] (2) adding an environmentally friendly plasticizer, an ultraviolet absorber, a light stabilizer and an antioxidant to the first mixture obtained in step (1) in sequence, stirring and mixing at high speed for 10 min at 25° C., the stirring speed is 900 r / min, the temperature is raised to 120° C., and stirring and mixing at low speed for 2 hours at a stirring speed of 150 r / min under a vacuum degree of 0.01 MPa to obtain a second mixture;

[0107] (3) cooling the second mixture obtained in step (2) to 35° C., reducing the pressure by nitrogen, adding a dehydrating agent, evacuating, and stirring at medium speed for 15 min at 35° C. and a vacuum degree of 0.01 MPa at a speed of 450 r / min to obtain a third mixture;

[0108] (4) adding nitrogen to reduce the pressure, adding a silane coupling agent to the third mixture obtained in step (3), evacuating the mixture, stirring and mixing at a medium speed of 450 r / min at 35° C. and a vacuum degree of 0.01 MPa for 15 min, and obtaining a fourth mixture;

[0109] (5) Inflate with nitrogen to reduce the pressure, add a catalyst to the fourth mixture obtained in step (4), evacuate, and stir and mix at medium speed for 10 min at 35° C. and a vacuum degree of 0.01 MPa. The stirring speed is 450 r / min, and the formed paste is uniform, fine, and free of particles and gel, thereby obtaining the high-strength silane-modified polyether sealant.

[0110] Example 16

[0111] This embodiment provides a high-strength silane-modified polyether sealant and a preparation method thereof. The only difference between this embodiment and Example 1 is that the fumed silica (Evonik R-974) is replaced with fumed silica of the same mass (Tokuyama QS-10, Japan), and other conditions are the same as those in Example 1.

[0112] Comparative Example 1

[0113] This comparative example provides a one-component silane-modified polyether sealant and a preparation method thereof. The only difference between the comparative example and Example 1 is that no active nano-calcium carbonate is added, the weight portion of carbon black (HZ6004 series carbon black) is adjusted to 435 parts, and other conditions are the same as those in Example 1.

[0114] Comparative Example 2

[0115] This comparative example provides a one-component silane-modified polyether sealant and a preparation method thereof. The only difference between the comparative example and Example 1 is that no carbon black is added, the weight portion of active nano calcium carbonate (Japanese Bamboo Source SP) is adjusted to 435 parts, and the other conditions are the same as those in Example 1.

[0116] The high-strength silane-modified polyether sealants provided in Examples 1 to 16 and the one-component silane-modified polyether sealants provided in Comparative Examples 1 to 2 were tested as follows:

[0117] (1) Surface drying time: Tested in accordance with GB / T 13477.5-2002 "Test methods for building sealing materials Part 5: Determination of surface drying time";

[0118] (2) Curing speed: Tested in accordance with GB / T 32369-2015 "Determination of degree of curing of sealants";

[0119] (3) Viscosity: According to GB / T 2794-1995 “Standard for Determination of Viscosity of Adhesives”, the viscosity was measured using a rotational rheometer;

[0120] (4) Hardness: The high-strength silane-modified polyether sealant and the one-component silane-modified polyether sealant were cured for 168 h at a temperature of 23° C. and a humidity of 50%, and then tested in accordance with GB / T531.1-1999 “Rubber pocket hardness tester indentation hardness test method”;

[0121] (5) Density: The high-strength silane-modified polyether sealant and the one-component silane-modified polyether sealant were cured for 168 h at a temperature of 23° C. and a humidity of 50% and tested in accordance with GB / T 533-2008 “Determination of density of vulcanized rubber or thermoplastic rubber”;

[0122] (6) Adhesion without primer: According to GB / T 13477.18-2002 "Test methods for building sealing materials Part 18: Determination of peel adhesion", the sealant layer formed by curing high-strength silane-modified polyether sealant or one-component silane-modified polyether sealant and the test substrate are cut and peeled off with a blade. The sealant is firmly adhered to the test substrate, the bonding interface does not fall off and the failure is cohesive, which is considered excellent;

[0123] (7) Tensile strength and elongation at break: The high-strength silane-modified polyether sealant and the one-component silane-modified polyether sealant were cured for 168 h at 23°C and 50% humidity, respectively, and tested using a type 2 dumbbell in accordance with GB / T 528-2009 “Test method for tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”;

[0124] (8) Shear strength: The shear strength of 304 stainless steel and aluminum was tested in accordance with GB / T 7124-2008 “Test method for tensile shear strength of adhesives (rigid material to rigid material)”.

[0125] The test results are shown in Tables 1 and 2 below.

[0126] Table 1

[0127]

[0128] Table 2

[0129]

[0130] It can be seen from the contents of Table 1 and Table 2 that the high-strength silane-modified polyether sealant provided by Examples 1-16 has a viscosity of 260,000 to 345,000 MPa·s, a tensile strength of 3.1 to 4.6 MPa, an elongation at break of 180% to 300%, a shear strength of 304 stainless steel of 3.8 to 6.5 MPa, a shear sheet test failure type of ≥90% cohesive failure, a hardness of 62 to 68 HA, and has relatively excellent bonding properties for stainless steel substrates and aluminum substrates without primer.

[0131] Taking into account the cost of raw materials for the comprehensive product composition, product cost control, production and processing requirements, and mechanical properties requirements for construction application scenarios, the high-strength silane-modified polyether sealant prepared in Example 1 has the best mechanical properties, with a tensile strength of up to 3.5 MPa, a shear strength of up to 5.9 MPa for a 304 stainless steel substrate, a hardness of up to 66HA, and a relatively moderate elongation at break of 205%. The viscosity is as high as 332000 MPa·s, and is suitable for construction process sites with higher viscosity requirements, higher tensile strength and shear strength requirements, and instantaneous positioning, such as windshield bonding and sealing of vehicles, high-speed railways, aerospace, and military series.

[0132] Compared with Examples 1, 5 to 7, as the weight fraction of active nano-calcium carbonate increases, the tensile strength and shear strength of the prepared high-strength silane-modified polyether sealant increase.

[0133] Compared with Example 1, if the specific surface area of ​​fumed silica is too small (Example 16), the tensile strength and shear strength of the prepared high-strength silane-modified polyether sealant are reduced. It can be seen that the high-strength silane-modified polyether sealant prepared when the specific surface area of ​​fumed silica is within a specific range has better performance.

[0134] Compared with Example 1, if the active nano-calcium carbonate is not added and the weight portion of carbon black is adjusted to 435 parts (Comparative Example 1), the viscosity of the prepared high-strength silane-modified polyether sealant is too high and difficult to construct; if the carbon black is not added and the weight portion of active nano-calcium carbonate is adjusted to 435 parts (Comparative Example 2), the tensile strength and shear strength of the prepared high-strength silane-modified polyether sealant are low.

[0135] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a high-strength silane-modified polyether sealant and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high-strength silane-modified polyether sealant, characterized in that: The high-strength silane-modified polyether sealant comprises the following components in parts by weight: 290-360 parts of silane-modified polyether resin, 150-200 parts of environmentally friendly plasticizer, 300-400 parts of nano calcium carbonate, 100-110 parts of carbon black, 10-30 parts of fumed silica, 3-5 parts of ultraviolet absorber, 3-5 parts of light stabilizer, 3-5 parts of antioxidant, 15-20 parts of water remover, 15-25 parts of silane coupling agent and 4-6 parts of catalyst.

2. The high-strength silane-modified polyether sealant according to claim 1, characterized in that: The silane-modified polyether resin is a dimethoxysilane-terminated polyether resin; Preferably, the viscosity of the silane-modified polyether resin at 25° C. is 10,000 to 80,000 mPa·s.

3. The high-strength silane-modified polyether sealant according to claim 1 or 2, characterized in that: The environmentally friendly plasticizer includes any one of polyether polyol, di(2-propylheptyl)phthalate or diisononyl phthalate or a combination of at least two thereof.

4. The high-strength silane-modified polyether sealant according to any one of claims 1 to 3, characterized in that: The nano calcium carbonate is active nano calcium carbonate; Preferably, the whiteness of the active nano calcium carbonate is 95% to 99%; Preferably, the specific surface area of ​​the active nano calcium carbonate is 15 to 20 m 2 / g; Preferably, the oil absorption value of the active nano-calcium carbonate is 20 to 30 mL / 100 g; Preferably, the specific surface area of ​​the fumed silica is 150 to 190 m 2 / g.

5. The high-strength silane-modified polyether sealant according to any one of claims 1 to 4, characterized in that: The ultraviolet absorber includes any one of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole or 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole or a combination of at least two thereof; Preferably, the light stabilizer comprises any one of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidinyl) succinate or poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]} or a combination of at least two thereof; Preferably, the antioxidant includes any one of glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] or tris[2,4-di-tert-butylphenyl] phosphite or a combination of at least two thereof.

6. The high-strength silane-modified polyether sealant according to any one of claims 1 to 5, characterized in that: The dewatering agent includes vinyl trimethoxy silane and / or vinyl triethoxy silane; Preferably, the silane coupling agent includes any one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, oligomeric bisaminosilane, multifunctional aminosilane oligomer, triaminotrimethoxysilane or bis(trimethoxysilylpropyl)amine, or a combination of at least two thereof; Preferably, the catalyst comprises any one or a combination of at least two of dibutyltin bis(acetylacetonate), dibutyltin dilaurate, dibutylbis(2,4-glutarato-O,O')-(OC-6-11)-tin or a reaction product of tetraethyl silicate and bis(acetyloxy)dibutyltinane.

7. A method for preparing the high-strength silane-modified polyether sealant according to any one of claims 1 to 6, characterized in that: The high-strength silane-modified polyether sealant comprises the following steps: mixing silane-modified polyether resin, environmentally friendly plasticizer, nano calcium carbonate, carbon black, fumed silica, ultraviolet absorber, light stabilizer, antioxidant, dehydrating agent, silane coupling agent and catalyst to obtain the high-strength silane-modified polyether sealant.

8. The preparation method according to claim 7, characterized in that: The high-strength silane-modified polyether sealant specifically comprises the following steps: (1) mixing a silane-modified polyether resin, nano-calcium carbonate, carbon black, and fumed silica to obtain a first mixture; (2) mixing the first mixture obtained in step (1), an environmentally friendly plasticizer, an ultraviolet absorber, a light stabilizer and an antioxidant to obtain a second mixture; (3) mixing the second mixture obtained in step (2) with a water removing agent to obtain a third mixture; (4) mixing the third mixture obtained in step (3) with a silane coupling agent to obtain a fourth mixture; (5) Mixing the fourth mixture obtained in step (4) with a catalyst to obtain the high-strength silane-modified polyether sealant.

9. The preparation method according to claim 8, characterized in that: The mixing in step (1) is carried out under a vacuum degree of -0.09 to 0.1 MPa; Preferably, the mixing temperature in step (1) is 0 to 50°C; Preferably, the mixing in step (1) is stirring mixing, the stirring speed is 900-1000 r / min, and the time is 30-40 min; Preferably, the mixing in step (2) comprises stirring and mixing at 0-50° C. and a rotation speed of 900-1000 r / min for 5-12 min, then heating to 100-120° C., stirring and mixing for 2-3 h under the conditions of a vacuum degree of -0.09-0.1 MPa and a rotation speed of 150-250 r / min; Preferably, the mixing in step (3), step (4) and step (5) is independently carried out under a vacuum degree of -0.09 to 0.1 MPa; Preferably, the mixing temperatures in step (3), step (4) and step (5) are each independently ≤ 45°C; Preferably, the mixing in step (3) is stirring mixing, the stirring mixing speed is 400 to 500 r / min, and the stirring mixing time is 10 to 18 min; Preferably, the mixing in step (4) is stirring mixing, the stirring mixing speed is 400 to 500 r / min, and the stirring mixing time is 10 to 18 min; Preferably, the mixing in step (5) is stirring mixing, the stirring mixing speed is 400-500 r / min, and the stirring mixing time is 5-12 min.

10. Use of the high-strength silane-modified polyether sealant according to any one of claims 1 to 6 in windshield bonding.

Citation Information

Patent Citations

  • Silicone sealant for automobile side windscreen and preparation method thereof

    CN104099059A

  • High-elasticity silane modified polyether sealant and preparation method of same

    CN107603549A

  • High-strength silane modified block polyether elastic sealant and preparation method thereof

    CN108130033A

  • High-strength silane-modified polyether sealant for automobiles and preparation method thereof

    CN108753233A

  • High-strength equal-proportion silane modified polyether sealant and preparation method thereof

    CN110951435A